Beedi Leaf Industry in Orissa - Mohanty, A. P. (Indian Forester, 1952)
In Beedis the leaves of Diospyros meianoxylon ( Kendu-Odya ) are almost universally used for wrapping tobacco. Kendu is common throughout Orissa. With the increase in popularity cf Beedis the Kendu leaf industry has immensely developed, and in many forest divisions of Orissa it is one of the principal source of revenue. In this article, the reason of Kendu leaves being suitable for Beedi making, the sale and all aspects of Kendu leaf collections has been briefly described.